2010
DOI: 10.1155/2011/340639
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Aluminium in Acid Media By Citrullus Colocynthis Extract

Abstract: Inhibition of corrosion of aluminium in acid solution by methanol extract ofCitrullus colocynthisplant has been studied using mass loss and thermometric measurements. It has been found that the plant extract act as a good corrosion inhibitor for aluminium in all concentrations of sulphuric and hydrochloric acid solution. The inhibition action depends on the concentration of acid and inhibitor. Results for mass loss and thermometric measurement indicate that inhibition efficiency increase with increasing inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
3
17
0
Order By: Relevance
“…The k value increases with rising temperature. At each temperature, a linear variation was observed in the presence of EEPgS, thus confirming a first order kinetics [30].…”
Section: Kinetic Treatment Of Weight Loss Resultssupporting
confidence: 69%
“…The k value increases with rising temperature. At each temperature, a linear variation was observed in the presence of EEPgS, thus confirming a first order kinetics [30].…”
Section: Kinetic Treatment Of Weight Loss Resultssupporting
confidence: 69%
“…Adsorption isotherms such as Langmuir, Freundlich, Frumkin and Temkin have been used by various authors for the description of adsorption equilibrium. 6,29,35,36) Febrianto et al 36) reported that Temkin isotherm is superior in the prediction of gas phase equilibra, while Freundlich isotherm has the ability to fit nearly all experimental adsorption data. Langmuir adsorption isotherm is used when it is assumed that the inhibitors adsorbed on the metal surface decrease the surface area available for metallic corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…The use of natural products as corrosion inhibitors have been reported by several research scientists. Numerous naturally occurring products such as Prosopis juliflora 4 , Lawsonia 5 , Calotropis 6 , Acacia senegal 7 , Citrullus colocynthis 8 , Aloes 9 , Tagetes erecta 10 , Retama monosperma 11 and Canna indica 12 plant extracts have been evaluated as effective corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%